Studies of seals and seabirds on Bouvetøya 2000/01 - fieldwork and preliminary results - Krafft, Bjørn; Hofmeyr, Greg J G; Keith, Dave; Harck, Bianca I B; Kovacs, Kit M (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Bouvetøya; NARE 2000/01; biologi; fugler; ornitologi; seler; zoologi

Distribution and food consumption of Ross seals (Ommatophoca rossii) and Leopard seals (Hydrurga leptonyx) - Nordøy, Erling S; Blix, Arnoldus Schytte (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; havis; marin biologi; seler; sjøis; zoologi

The gastrointestinal tract of Adélie penguins – morphology and function - Olsen, Monica; Myklebust, Reidar; Kaino, Turid; Elbrønd, Vibeke; Mathiesen, Svein (Polar Biology, 2002)
Keywords: Antarktis; pingviner; zoologi

Studies of population dynamics and life history strategies of Antarctic petrels at Svarthamarehn - Tveraa, Torkild; Birkeland, Ingve; Henden, John-André; Varpe, Øystein (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Dronning Maud Land; NARE 2000/01; fugler; ornitologi; petreller; zoologi; økologi

Body Condition and Parental Decisions in the Snow Petrel (Pagodroma nivea) - Tveraa, Torkild; Guttorm, N. Christensen (The Auk, 2002)
In Procellariiformes, parents guard the chick for some time after it has attained homeothermy. Such a strategy may have evolved to protect the chick from predation or inclement weather, but it is costly because only one parent can forage at a time. Therefore, the decision to leave the chick seems to be a trade-off between the chick's ability to care for itself, body condition of the parent present at the nest, and ability of the bird out foraging to return to the nest before its mate's body condition has degraded. We studied chick growth and survival together with number of days Snow Petrel (Pagodroma nivea) chicks were guarded before being left alone for the first time in relation to the parents body condition and ability to return to the nest in time. Parents in good body condition were more likely to produce a chick that survived the guard stage. They also guarded their chick for a longer period (range 2–8 days, x̄ = 4.5) and finally left it alone with a higher body mass than those in poor body condition. However, whether the foraging bird was able to return to the nest in time to relieve its mate was also strongly related to number of days the chick was guarded and its body mass. The chicks' survival from when they were left alone and until day 10 posthatch was positively related both to number of days they were guarded and their body condition (body mass corrected for age).
Keywords: Antarktis; fugler; ornitologi; petreller; zoologi